Jakub z Paradyża – protoreformator? Introdukcja do badań na kanwie traktatu O trzech rodzajach ludzi – zwierzchnikach, aktywnych i kontemplatykach - Słowiński, Przemysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The main considerations related to the subject matter of the article were preceded by a comprehensive introduction, in which the figure of Jakub from Paradyż, who is the greatest thinkers, not only Polish, but European of his time, was presented. He was a scholar who had a significant influence on the development of science in the Middle Ages. Because of its timelessness, it’s thought can still be a model for future generations. Jakub from Paradyż devoted his life to science. He perceived the value of these teachings that teach proper life and directed his writings to a wide range of recipients. The intellectual values that characterized this outstanding philosopher were recorded in about 150 treaties, sermons and lectures. Some of his views are presented in the article below, presenting theses taken from the title treaty.